Next-generation mobile satellite networks. - Del Re, E. (IEEE Communications magazine)
Due to the increasing demands of multimedia services supporting high bit rates and mobility, ATM, TCP/IP, and satellite technology are going to be associated to form the internetwork infrastructure of future global systems. In this scenario, distinctions between terrestrial and satellite communications systems, as well as between fixed networks and 3G mobile networks, will cease to exist in a global coverage wireless system. The European Action COST252 actively participated in developing the satellite component of UMTS